2023
DOI: 10.1016/j.jvoice.2020.12.042
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Impact on the Musician and Returning to Singing; A Literature Review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Singers have a sophisticated use of vocal adjustments and are at risk of developing voice disorders, regardless of whether they are professionals or amateurs 12,13 . The COVID-19 pandemic has changed the routine of these singers due to social isolation and reduced singing activities, which may have impacted their lives and voices 15 in the functional, professional, financial, physical, and emotional domains 5 . A study showed that among the aspects most affected by the COVID-19 pandemic, the social bond has a more substantial weight in the perception of loss during routine changes in the COVID-19 pandemic in amateur singers, while professional singers miss physical experiences, physical training, voice training and breathing training 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singers have a sophisticated use of vocal adjustments and are at risk of developing voice disorders, regardless of whether they are professionals or amateurs 12,13 . The COVID-19 pandemic has changed the routine of these singers due to social isolation and reduced singing activities, which may have impacted their lives and voices 15 in the functional, professional, financial, physical, and emotional domains 5 . A study showed that among the aspects most affected by the COVID-19 pandemic, the social bond has a more substantial weight in the perception of loss during routine changes in the COVID-19 pandemic in amateur singers, while professional singers miss physical experiences, physical training, voice training and breathing training 29 .…”
Section: Discussionmentioning
confidence: 99%
“…There is little information about how the virus is transmitted during the singing and how to return to this activity in person safely 5,14 . However, there seems to be a risk of transmitting the SARS-CoV-2 virus through an exhalation act, and that singing, especially singing with increased amplitude, would project more aerosols than other speech events 15 .…”
Section: Introductionmentioning
confidence: 99%
“…It is very interesting to note that from eight singers (soloist or choir) who had been tested positive during the entire study period, only one presumably caused two further infections within the Bavarian State Opera (cases 59 and 60). Especially considering that singing has been shown to generate significantly more aerosols than normal talking and breathing described in the literature [ 35 , 36 , 37 , 38 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Students may also have concerns that their ability to participate in sports, as a result of wearing masks, must be curtailed, although cloth masks have been found to have no effect on vigorous exercise performance in healthy individuals [166]. For those students involved with vocal music, the effect of othering has been intense, having a major impact on their sense of self [167].…”
Section: Protecting the Self-mask-wearing In Personal Spacementioning
confidence: 99%